Utilization of Digitalization as Support for Pregnant Women in Preventing Anemia in Majungan Village - Qurrotu Aini; Layla Imroatu Zulaikha (International Journal of Public Devotion, 2026)
Anemia in pregnant women is a public health problem that remains high in Indonesia, especially in rural areas. Based on data from the 2018 Basic Health Research (RisKesDas), the prevalence of anemia in pregnant women reached 48.9%. One cause of anemia is the low level of knowledge of mothers about the importance of consuming iron tablets (TTD). The purpose of this community service activity is to improve the knowledge and behavior of pregnant women in preventing anemia through a digital approach. The media used is the WhatsApp application, namely by creating a special group to assist pregnant women in consuming iron tablets, which is monitored and reminded regularly. The measurement tool used in this assistance is a questionnaire on knowledge about anemia and compliance with iron tablets. The results of the activity showed a significant increase in pregnant women's knowledge about anemia and the importance of iron tablets (TTD). Pregnant women became more compliant and routine in consuming iron tablets. Digital-based assistance has proven effective in providing ongoing support to pregnant women, especially in areas with limited access to health facilities.Pemanfaatan Digitalisasi Sebagai Pendampingan Ibu Hamil Dalam Pencegahan Anemia Di Desa MajunganABSTRAKAnemia pada ibu hamil merupakan salah satu masalah kesehatan masyarakat yang masih tinggi diindonesia,terutama wilayah pedesaan. Berdasarkan data Riset Kesehatan Dasar (RisKesDas) tahun 2018, prevelansi anemia pada ibu hamil mencapai 48,9%. Salah satu penyabab anemia adalah rendahnya tingkat pengetahunan ibu tentang pentingnya konsumsi tablet tambah darah (TTD). Tujuan kegiatan pengabdian ini untuk meningkatkan penegtahuan dan perilaku ibu hamil dalam mencegah anemia melalui pedekatan digital. Media yang digunakan adalah aplikasi whatsapp yaitu dengan membuat grup khusus pendampingan pada ibu hamil dalam mengonsumsi tablet tambah darah yang dipantau dan diingatkan secara berkala. Alat ukur yang digunakan dalam pendampingan ini berupa kuesioner pengetahuan tentang anemia dan kepatuhan minum TTD. Hasil kegiatan menunjukkan peningkatan yang signifikan dalam pengetahuan ibu hamil tentang anemia dan pentingnya tablet tambah darah (TTD). Ibu hamil menjadi lebih patuh dan rutin dalama mengkonsumsi TTD. Pendampingan  berbasis digital terbukti efektif dalam memberikan dukungan berkelanjutan pada ibu hamil terutama pada daerah dengan keterbatasan akses terhadap fasilitas kesehatan.Kata Kunci :Anemia;Ibu Hamil; Pendampingan; Digitalisasi